Naturalistic and Uncontrolled Pilot Study on the Efficacy of Vortioxetine in Binge Eating Disorder With Comorbid Depression - Segura-Garcia, Cristina; Rania, Marianna; Carbone, Elvira Anna; de Filippis, Renato; Aloi, Matteo; Caroleo, Mariarita; Grasso, Gloria; Calabrò, Giuseppina; Fazia, Gilda; Staltari, Filippo Antonio; Falvo, Antonella; Pugliese, Valentina; et al. (Frontiers in Psychiatry, 2021)
Background. Binge eating disorder (BED) is clinically relevant by virtue of the global impairment, poor quality of life and increased overall medical morbidity. The high comorbidity with psychiatric disorders, particularly depression, has received attention as a possible mediator of the poor outcome. Further, BED and depression share cognitive dysfunctions. This naturalistic and uncontrolled pilot study aimed at evaluating the efficacy of vortioxetine (VTX) on depressive symptoms in patients with BED, secondly the efficacy in improving a broad array of executive functions, and third to explore the effect on eating behaviour and body weight. Methods. This pilot study involved 30 patients with BED and comorbid MDD, treated with VTX for 24 weeks. Assessments were run at baseline (t0), 4 (t1), 8 (t2), 12 (t3) and 24 (t4) weeks. Changes in depressive symptoms (HDRS and BDI), executive functions, eating behaviours (binge frequency and severity, night eating, food addiction) and body weight were estimated after treatment with VTX through GLM. Results. Significant improvements emerged after treatment with VTX in: depression (HDRS p < 0.001; BDI-II p = 0.002) regardless the dose of VTX and first diagnosis (BED/MDD), working memory (RAVLT acquisition p = 0.01 and delay recall p < 0.001, RCFT percentage of recall p = 0.01 and Attentional Matrices p = 0.05), binge days frequency (p<0.001), binge eating severity (BES p < 0.001), night eating (p = 0.001), food addiction (YFAS 2.0 p = 0.039), and body weight (p = 0.039). The improvement in depressive symptoms was associated with the concurrent improvement in night eating as assessed by the I-NEQ. Conclusions. VTX can be a valid therapeutic choice for patients with BED with comorbid depression in controlling the depressive symptoms, working memory and eating behaviour. Indeed, by acting on affective symptoms, neurocognitive functioning and eating behaviours, it confirms the results already obtained with VTX in other disorders, expanding them to BED.